performance of broiler chicks fed cottonseed cake-based diets (2004)
"The potential of Cottonseed cake (CSC) at 0%, 25%, 50%, 75% and 100% replacement for Soybean cake (SBC) as an alternative protein source in chicks was investigated. One hundred and eighty Anak broiler chicks at day old were divided into twelve groups and randomly assigned to the five dietary treatments with three replicates per treatment. The feeding trial lasted for four weeks at the teaching and research farm of the university of Ibadan Nigeria. Feed intake revealed that chicks fed cottonseed cake-based diets had higher consumption when compared to those fed control. Though feed conversion showed significant differences (P<0.05) it did not follow a particular trend. There were significant (P<0.05) differences in protein utilization across the treatments. The highest protein efficiency ratio (PER) values were obtained with the birds in diet 3 (50% CSC) with values of 2.78 and 2.84 respectively while diet 5 (100% CSC) gave the lowest value of 1.20. Results showed there were significant (P<0.05) differences in weight gain from the 1st week to the 411' week. Birds fed diet 4 having 75% CSC replacement for SBC had the same value (220g) with the control (Diet 1) Mortality was low in all the treatments and a range of 1-2 % mortality was recorded during the study. "